The expansion of the personal name authority record under Resource Description and Access: Current status and quality considerations. (March 2015) - Moulaison, Heather Lea
Persons are complex, and their representation in library authority records is becoming increasingly sophisticated through the addition of attributes under Resource Description and Access rules. This case study, using a longitudinal approach, examines attributes in authority records from the MERLIN cluster of academic libraries at both six months (i.e. September 2013) and one year (i.e. April 2014), after the official adoption of RDA to assess trends in attribute field usage. After one year of Resource Description and Access cataloging, this study investigates the metadata quality indicator of completeness. Overall, attributes supplied tend to be sparse; 87.58% of authority records had no attributes at all, but the number of records with content had increased over the previous six months. Almost 8% of authority records had at least one attribute after a year; and almost 5% had two or more attributes.